Limits of economic and social knowledge - DeCanio, Stephen J.; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
The book aims to show that the deterministic vision embodied in conventional economic modelling is neither consistent with nor supported by the state of the art in mathematics, logic, and physical science. DeCanio recognizes that economic agents are intrinsically free and somewhat unpredictable, which is essential for economic and social theory.
Keywords: Science